Etude de la dynamique interne des communautés d’apprentissage professionnelles dans l’enseignement primaire au Sénégal. - Cyrielle Le Her (Éducation et Socialisation)
According to the research of Lave and Wenger (1991) and Stoll et al. (2006), participation in communities of professionals can be a factor favoring teachers’ professional development. However, over the past ten years or so, zonal pedagogical animation cells in primary education in Senegal have lacked dynamism (Wallet and Diop, 2017). Thus, the article focuses on 21 individual semi-structured interviews with teachers in the academies of Dakar, Ziguinchor and Sédhiou face-to-face in January 2022. Despite attempts at revitalization, the results of the study show the similar findings as those drawn from the 2017 study (Wallet and Diop, 2017). Yet the zonal pedagogical animation cells continue to function and attract the presence of in-house teachers. The reason for the scheme’s continued existence seems to be the impetus given to new dynamics in the communities by the often individual remediation initiatives of motivated teachers (Crozier and Friedberg, 1977). This article provides a better understanding of the causes of the lack of dynamism mentioned above, and the strategies put in place by the players to continue professionalizing through collaboration.